Contrasting Nitrogen Fertilisation Rates Alter Mycorrhizal Contribution to Barley Nutrition in a Field Trial - Thirkell, Tom; Cameron, Duncan; Hodge, Angela (Frontiers in Plant Science, 2019)
Controlled environment studies show that arbuscular mycorrhizal fungi (AMF) may contribute to plant nitrogen (N) uptake, but the role of these near-ubiquitous symbionts in crop plant N nutrition under natural field conditions remains largely unknown. In a field trial, we tested the effects of N fertilisation and barley (Hordeum vulgare L.) cultivar identity on the contribution of AMF to barley N uptake using 15N tracers added to rhizosphere soil compartments. AMF were shown capable of significantly increasing plant 15N acquisition from root exclusion zones, and this was influenced by nitrogen addition type, N fertiliser application rate and barley cultivar identity. Our data demonstrate a previously overlooked potential route of crop plant N uptake which may be influenced substantially and rapidly in response to shifting agricultural management practices.